Surface tailored spent coffee ground derived carbon reinforced waste HDPE composites for 3D printing application - Sushrisangita Sahoo; Abhinav Yadav; Vijaya Rangari (Composites Part C: Open Access)
The serious impact of plastic waste on environmental pollution and climate change led to new strategies like recycle, reuse, reduce concept. This work presents a unique sustainable approach of developing filament composites with improved thermal and mechanical properties by mixing the plastic waste (i.e. waste Walmart bag, High Density Polyethylene (HDPE)) and surface engineered spent coffee ground (SCG) waste derived carbon. Carbon as filler materials were obtained by pyrolyzing the SCG waste. As the biomass derived carbon generally has inert surface properties, it causes poor compatibility between the filler and polymer matrix yielding inferior thermal and mechanical properties of the composites. So, the properties of pyrolyzed carbon in the present work were tailored by SF6 plasma treatment at different time durations. The surface functionalization of carbon materials and optimized plasma treatment time were analyzed from different characterizations. Fourier Transform Infrared Spectroscopy (FTIR) and X-ray Photoelectron Spectroscopy (XPS) reveals 15 min plasma treatment carbon is the optimized one with highest fluorination and semi-ionic C-F bonding. Due to the highest fluorination, the ID/IG ratio i.e. the defect density is found to be maximum for 15 min plasma treated carbon from the Raman spectra. The 15 min plasma treated carbon with highest fluorine functionalization as a filler exhibits 33.8 % and 13.97 % improvement in tensile modulus and tensile strength in comparison to neat HDPE matrix. The feasibility test of filament composites for 3D printing suggests its application potentiality in Material extrusion (MEX) 3D printing.